2009
DOI: 10.1159/000232975
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Axis I Antecedents before Age 18 of Unipolar Depression, Bipolar Disorder and Schizophrenia

Abstract: Background: Despite a large scientific literature on early clinical precursors of schizophrenia, bipolar disorder and unipolar depression, few data are available on axis I disorders preceding the adult onset of these illnesses. Sampling and Methods: Disorders before the age of 18 years were retrospectively assessed with a structured interview in 3 groups of consecutive adult inpatients with DSM-IV diagnoses of schizophrenia (n = 197), major depressive disorder (n = 287) and bipolar disorder (n = 132). Only pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 89 publications
0
30
0
Order By: Relevance
“…In the prospective longitudinal study of KimCohen et al [15] , more than 50% of adults with schizophrenia met the criteria for another psychiatric disorder in early adolescence, and ADHD, conduct disorder and oppositional defiant disorder were, among them, the most frequently reported. Moreover, a retrospective study performed by Rubino et al [16] found that a diagnosis of ADHD in childhood was most predictive of schizophrenia in adulthood compared to unipolar depression. Followup studies focusing on adult outcome of childhood ADHD [17,18] confirmed that youth with ADHD constitute a high risk group for developing a wide range of psychiatric diseases [17] , and that children and adolescents with ADHD were 4.3 times more likely to develop schizophrenia later in adulthood compared to controls [18] .…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…In the prospective longitudinal study of KimCohen et al [15] , more than 50% of adults with schizophrenia met the criteria for another psychiatric disorder in early adolescence, and ADHD, conduct disorder and oppositional defiant disorder were, among them, the most frequently reported. Moreover, a retrospective study performed by Rubino et al [16] found that a diagnosis of ADHD in childhood was most predictive of schizophrenia in adulthood compared to unipolar depression. Followup studies focusing on adult outcome of childhood ADHD [17,18] confirmed that youth with ADHD constitute a high risk group for developing a wide range of psychiatric diseases [17] , and that children and adolescents with ADHD were 4.3 times more likely to develop schizophrenia later in adulthood compared to controls [18] .…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…Prevalence estimations of OCS in samples at ultra high risk for psychosis [54,55] or in first episode patients (FEP) [56] are considerably lower. Reported comorbidity rates range from 7% in a sample of 200 FEPs [42] over 9.3% in 193 [57] up to 14% in 50 FEPs [56].…”
Section: Epidemiologymentioning
confidence: 99%
“…For example, childhood ADHD is associated with adult onset schizophrenia and bipolar disorder [33]. Concordant with this finding, attentional impairment is a core deficit in schizophrenia [34], and there is strong evidence that it is an endophenotype of the disorder [35,36].…”
Section: Diagnosis and Treatment Of Attention Disordersmentioning
confidence: 85%